Strategies for COVID-19 vaccination under a shortage scenario: ageo-stochastic modelling approach - Barreiro, N. L. (2021)
In a world being hit by waves of COVID-19, vaccination is a light on the horizon. However, the roll-out of vaccination strategiesand their influence on the pandemic are still open problems. In order to compare the effect of various strategies proposed bythe World Health Organization and other authorities, a previously developed SEIRS stochastic model of geographical spreadingof the virus is extended by adding a compartment for vaccinated people. The parameters of the model were fitted to describethe pandemic evolution in Argentina, Mexico and Spain to analyze the effect of the proposed vaccination strategies. Themobility parameters allow to simulate different social behaviors (e.g. lock-down interventions). Schemes in which vaccines areapplied homogeneously in all the country, or limited to the most densely-populated areas, are simulated and compared. Thesecond strategy is found to be more effective. Moreover, under the current global shortage of vaccines, it should be remarkedthat immunization is enhanced when mobility is reduced. Additionally, repetition of vaccination campaigns should be timedconsidering the immunity lapse of the vaccinated (and recovered) people. Finally, the model is extended to include the effect ofisolation of detected positive cases, shown to be important to reduce infections.